Public Relations & Media Relations (Kritik Budaya Amplop Pada Media Relations Institusi Pendidikan Di Yogyakarta) - Adhianty Nurjanah; Wulan Widyasari; Frizky Yulianti N (Jurnal Komunikasi, 2015)
AbstractThis research is aims to determine how the media relations activities that have been done 10 Public Relations Higher Education, including the possibility of granting cultural envelope in media relations activities during this do. The object of this study is ten (10) Universities in Yogyakarta that consists of three (3) State University (PTN) and seven (7) Colleges (PTS). Variations and types of media relations activities have been conducted by 10 universities. The reason is because the electoral college to ten (10) college is a big college in the city of Yogyakarta who own Public Relations and media relations activities that have a systematic and well-planned. In the course of media relations,  Public Relations universities do culture accepting envelopes to reporters on the grounds reimburse the costs of transport and not as a "bribe" so that they publicized the news and as a means of imaging the institution. Publicist colleges feel that culture provides envelopes to reporters did not violate the code of ethics of their profession as a Public Relations, On the other hand for journalists, cultural granting envelope can interfere with the independence and constitute a violation of the code of ethics of their profession as journalists. Yet there are also journalists who will receive an envelope in their reporting activities. The discrepancies in the implementation of the code of ethics of journalism, is strongly influenced by the integrity of journalists and policies that apply to each media institution.AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana kegiatan media relations yang telah dilakukan 10 Public Relations / Humas Perguruan Tinggi tersebut, termasuk kemungkinan adanya budaya pemberian amplop dalam kegiatan media relations yang selama ini dilakukan.  Objek penelitian ini adalah sepuluh (10) Perguruan Tinggi di Yogyakarta yang terdiri dari tiga (3) Perguruan Tinggi Negeri (PTN) dan tujuh (7) Perguruan Tinggi Swasta (PTS) . Beragam variasi dan jenis kegiatan media relations telah dilakukan oleh 10  perguruan tinggi tersebut. Alasan pemilihan perguruan tinggi tersebut dikarenakan ke sepuluh (10) perguruan tinggi tersebut merupakan perguruan tinggi yang besar di Kota Yogjakarta yang sudah memiliki Public Relations dan mempunyai kegiatan media relations yang tersistematis dan terencana. Dalam kegiatan media relations, Public Relations perguruan tinggi melakukan budaya pemberian amplop kepada wartawan dengan alasan mengganti biaya transportasi dan bukan sebagai “uang sogok” agar berita mereka terpublikasikan dan sebagai sarana pencitraan institusi. Public Relations perguruan tinggi merasa bahwa budaya memberikan amplop kepada wartawan tidak melanggar kode etik profesi mereka sebagai Public Relations. Dilain pihak bagi wartawan, budaya pemberian amplop dapat mengganggu independensi dan merupakan bentuk pelanggaran kode etik profesi mereka sebagai wartawan. Meskipun demikian masih ada juga wartawan yang mau menerima amplop dalam kegiatan peliputan mereka. Adanya perbedaan dalam mengimplementasikan kode etik profesi jurnalistik, sangat dipengaruhi oleh integritas wartawan dan kebijakan yang berlaku pada masing-masing institusi media.